The enduring significance of Parmenides : unthinkable thought - Tallis, Raymond (Continuum studies in ancient philosophy., 2007)
Parmenides of Elea is widely regarded as the most important of the Presocratic philosophers and one of the most influential thinkers of all time. He is famous, or notorious, for asserting that change, movement, generation and perishing are illusions arising from our senses, that past and future do not exist, and that the universe is a single, homogeneous, static sphere. This picture of the world is not only contrary to the experience of every conscious moment of our lives, it is also unthinkable, since thoughts themselves are events that come into being and pass away. In this important new boo.